PENGUATAN DUKUNGAN SOSIAL INTERGENERASI MELALUI PROGRAM VOLUNTEER MAHASISWA DI PANTI WHERDA BUMI PERTIWI BANDUNG UNTUK MENCAPAI SDG 10 (REDUCED INEQUALITIES) - Afipah, Septianis; Rizki, Diyah Pitaloka; Yuliani, Rostika (Unpad Press, 2025)
. Nursing homes' older occupants often experience a lack of interaction and a disconnect from younger people, which reinforces their feelings of loneliness and social isolation. The International Relations Study Program of Universitas Al Ghifari addressed this issue by organizing a community service activity at Panti Wredha Budi Pertiwi. The purpose of this activity was to strengthen intergenerational social support by students volunteering to partake in various activities with the elderly, in line with SDG 10 (Reduced Inequalities). The approach was community education in the form of light counselling and participatory activities. The elderly participants felt more enthusiastic and active in the social atmosphere while students gained useful experience, understanding the need for intergenerational social support. The program was able to create positive change and improve social engagement, although the discussion suggested the activities were relatively brief. Strengthening social ties was achieved with this day's activities.